2007
DOI: 10.1111/j.1469-8137.2007.02192.x
|View full text |Cite
|
Sign up to set email alerts
|

Sentinels at the wall: cell wall receptors and sensors

Abstract: Contents Summary 7 Introduction 8 Cell expansion and plant growth 8 Cell wall responses to stress 11 Pathogen attack and mechanical stimuli 11 Lessons from yeast 12 Candidate sensors and receptors in plants 14 Conclusions 17 Acknowledgements  17 References  17 Summary The emerging view of the plant cell wall is of a dynamic and responsive structure that exists as part of a continuum with the plasma membrane and cytoskeleton. This continuum must be responsive and adaptable to normal processes of growth as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
162
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(165 citation statements)
references
References 171 publications
(197 reference statements)
1
162
0
2
Order By: Relevance
“…This suggests that fei1 fei2 perturbs the biosynthesis or function of cellulose. Consistent with this, the roots of fei1 fei2 seedlings grown in nonpermissive conditions produced ectopic lignin ( Figure 1H), which is generally correlated with a decreased level of crystalline cellulose (Humphrey et al, 2007). We further analyzed cellulose synthesis by measuring the incorporation of [ 14 C]glucose into crystalline and noncrystalline cellulosic cell wall fractions of excised root tips.…”
Section: The Fei1 Fei2 Mutant Is Defective In Cellulose Biosynthesismentioning
confidence: 66%
“…This suggests that fei1 fei2 perturbs the biosynthesis or function of cellulose. Consistent with this, the roots of fei1 fei2 seedlings grown in nonpermissive conditions produced ectopic lignin ( Figure 1H), which is generally correlated with a decreased level of crystalline cellulose (Humphrey et al, 2007). We further analyzed cellulose synthesis by measuring the incorporation of [ 14 C]glucose into crystalline and noncrystalline cellulosic cell wall fractions of excised root tips.…”
Section: The Fei1 Fei2 Mutant Is Defective In Cellulose Biosynthesismentioning
confidence: 66%
“…This enzyme catalyzes the synthesis of rhamnose, which is a prominent component of cell wall pectin. In angiosperms, pectins have been linked to communication between cell wall and cytoplasm, particularly during periods of stress (Humphrey et al, 2007), although it remains to be demonstrated to what extent this holds for bryophytes. Evidently, P. patens survives desiccation with several strategies; how the moss combines these strategies still needs to be determined.…”
Section: Alterations In Cellular Structure Help To Limit Desiccation mentioning
confidence: 99%
“…Expansins are a superfamily of plant proteins involved in cell wall extension and stress relaxation, abscission, fruit softening, the response to biotic and abiotic stresses, and development of leaf, floral organ, root hairs and grain size [8,9,[17][18][19][20][21][22][23][24][25][26][27][28]. Expansins are subdivided into four families: a-expansin, b-expansin, expansin-like A and expansin-like B [29].…”
Section: Application To Expansins: An Isotropic Casementioning
confidence: 99%